(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
There is an increasing challenge to the marketing manager to develop and implement an integrated marketing communication (IMC) plan to realize the true value of the celebrity endorsements. There is a gradual shift from the traditional approach of showing celebrities in advertisement to making them the “spokes-person” of the brand. Companies have taken celebrity endorsement to next level by projecting brands as a way of life. Smart companies are using their brand ambassadors in other mediums such as movies to promote their brands. The research was exploratory and descriptive in nature. The research design was characterized by flexibility in order to be sensitive to the unexpected and to discover insight not previously recognized. Secondary and Primary data was collected and then analyzed.